2019
DOI: 10.23736/s0022-4707.18.08318-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbohydrate, ketogenic diet impairs anaerobic exercise performance in exercise-trained women and men: a randomized-sequence crossover trial

Abstract: A copyedited and fully formatted version will be made available soon. The final version may contain major or minor changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…Because the varied diet used by volunteers could affect the anaerobic power (Wroble et al, 2018) and the level of adipocytokines in the blood (Reis et al, 2010; de Luis et al, 2016; Huang et al, 2017), the meal guidelines were proposed in our studies by a dietician taking the age, sex, and physical activity of the participants into account (2800 kcal/day for man, 2000 kcal/day for women; carbohydrates 55%, fat 30%, and proteins 15%) (Jarosz, 2017). The diet was assessed based on the analysis of dietary diaries filled in by the participants using the product and food photography album (Szponar et al, 2012) during the 7 days preceding the cycling sprint.…”
Section: Methodsmentioning
confidence: 99%
“…Because the varied diet used by volunteers could affect the anaerobic power (Wroble et al, 2018) and the level of adipocytokines in the blood (Reis et al, 2010; de Luis et al, 2016; Huang et al, 2017), the meal guidelines were proposed in our studies by a dietician taking the age, sex, and physical activity of the participants into account (2800 kcal/day for man, 2000 kcal/day for women; carbohydrates 55%, fat 30%, and proteins 15%) (Jarosz, 2017). The diet was assessed based on the analysis of dietary diaries filled in by the participants using the product and food photography album (Szponar et al, 2012) during the 7 days preceding the cycling sprint.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite several promising results in favor of improved performance during exercise of moderate intensity, there is a lack of ambiguous evidence to support the benefits of HFD in anaerobic endurance in athletes [14,17]. There are also studies that revealed a negative impact of an HFD on exercise performance in healthy sedentary adults [18,19]. Thus, HFD potentially compromises physical performance during high-intensity exercises and thereby may fail implementation of a training program based on such exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, exercise can play an important role in the management of diabetes and other metabolic dysfunction [109][110][111]. There is some evidence to suggest that an LCD or KD may impair exercise ability [112][113][114][115], although this is not consensus and may depend on exercise type [116][117][118]. Further studies on the role of ketosis and carbohydrate restriction on exercise capacity in patients with diabetes is warranted.…”
Section: Discussionmentioning
confidence: 99%